LOCAL ELECTIONS 2010, 2015 IN POLTAVA REGION: FEATURES OF EVOLUTION OF DECLARATION OF WILL - Vorona P.V. (Pressing Problems of Public Administration, 2016)
Іn the article the characteristics of the electoral process in poltava region is geopolitically plays a key rolein the development of Ukrainian statehood among other regions. Disclosed socio-political science andstatistical features of elections in the region and the role in this process of political parties, public movements.We analyze the electoral process, parliament as the Regional Council in 2010 and 2015 tracedthe evolution of the party to participate in local elections.